THE IMPACT OF CAREER PLANNING, EMPLOYEES’ AUTONOMY AND MANAGER RECOGNITION ON EMPLOYEES’ PRODUCTIVITY IN MANUFACTURING FIRMS - AMIN, BOKHORI MD (International Journal of Multidisciplinary Research and Studies, 2018)
This study investigated the effects of career planning, employees’ autonomy, and manager recognition on employee productivity. A survey of 222 employees in Penang manufacturing firms was conducted. A conceptual framework was developed to answer research questions about whether career planning, employee autonomy, and manager recognition contributed to employee productivity. In other words, the data confirmed the existence of a statistically significant relationship between independent variables: employee autonomy and manager recognition; and the dependent variable, employees’ productivity. Career planning was identified as a less significant contributor to employees’ productivity than the other two predictors. Managerial recognition is considered a better contributor, along with employees’ autonomy. These findings offer implications for research on employees’ productivity as an asset for manufacturing firms and suggest that in manufacturing firms, managers should have career planning discussions with their direct reports. These discussions set employees’ expectations for promotion and increase their level of productivity and involvement in the growth of manufacturing firms. Recognizing employees regularly for work well-done increases their sense of accomplishment towards the expected promotion, thus helping to ensure they always produce high productivity for manufacturing firms.